NPFFR2-deficient mice fed a high-fat diet develop strong intolerance to glucose - Karnošová, Alena; Strnadová, Veronika; Železná, Blanka; Kuneš, Jaroslav; Kašpárek, Petr; Maletínská, Lenka (Clinical science (London, England, 2023)
A previous study on neuropeptide FF receptor 2 (NPFFR2)-deficient mice has demonstrated that NPFFR2 is involved in the control of energy balance and thermogenesis. Here, we report on the metabolic impact of NPFFR2 deficiency in male and female mice that were fed either a standard diet (STD) or a high-fat diet (HFD) and each experimental group consisted of ten individuals. Both male and female NPFFR2 knockout (KO) mice exhibited severe glucose intolerance that was exacerbated by a HFD diet. In addition, reduced insulin pathway signaling proteins in NPFFR2 KO mice fed a HFD resulted in the development of hypothalamic insulin resistance. HFD feeding did not cause liver steatosis in NPFFR2 KO mice of either sex, but NPFFR2 KO male mice fed a HFD had lower body weights, white adipose tissues, and liver and lower plasma leptin levels compared with their wild-type (WT) controls. Lower liver weight in NPFFR2 KO male mice compensated for HFD-induced metabolic stress by increased liver PPARα and plasma FGF21 hepatokine, which supported fatty acid β-oxidation in the liver and white adipose tissue. Conversely, NPFFR2 deletion in female mice attenuated the expression of Adra3β and Pparγ, which inhibited lipolysis in adipose tissue.
Keywords: Insulin Resistance; Glucose; Male; inzulinová rezistence; Mice, Knockout; Obesity; tuková tkáň; obezita; glucose intolerance; Diet, High-Fat; mužské pohlaví; dieta s vysokým obsahem tuků; glukosa; bílá tuková tkáň; Adipose Tissue, White; insulin resistance; knockout mice; myši knockoutované; neuropeptide FF; Animals; Adipose Tissue; ženské pohlaví; játra; zvířata; porucha glukózové tolerance; myši inbrední C57BL; myši; high-fat diet; Mice, Inbred C57BL; Liver; Mice; Female; Glucose Intolerance